Aperfeiçoamento do ensaio de quantificação do RNA mensageiro da tiroglobulina por RT-PCR em tempo real no seguimento de pacientes com carcinoma diferenciado da tiróide - Boldarine, Valter Tadeu [UNIFESP] (2007)
ABSTRACT:The measurement of serum thyroglobulin(sTg)has been considered the most sensitive tumor marker in the follow-up of patients with differentiated thyroid carcinoma (DTC) after total thyroidectomy and radioiodine therapy. However, sTg assays present some technical problems, specially, the interference by endogenous anti-thyroglobulin antibodies(TgAb), present in approximately 20 por cento of DTC patients' sera. Therefore, in order to enhance sensitivity and to hinder the interference by TgAb, several investigators have tried to quantify the mRNA Tg by Real-Time RT-PCR. However, the results have been variable and some of them did not report a correlation between mRNA Tg measurement and presence of metastases.The aim of this study was to evaluate TgmRNA expression, performed by a new sensitive and specific Real-Time PCR, in peripheral blood of 104 patients who previously undergone total thyroidectomy and radioiodine treatment. DTC patients were studied during L-T4 therapy.Eighty-two patients out of 104(78.8 por cento)were considered “free of disease”, and 22(21.2 por cento) presented metastases.The quantification of mRNA was significantly different between patients “free of disease”and those with metastases:TgmRNA(90.1 vs 951.3 ug/uL)(P<0,0001).In conclusion, the differences proposed in the TgmRNA quantification made it a reliable method, and allowed us to differentiate patients free of disease from patients with metastases and thus could be an appropriate molecular marker in the follow-up of patients with thyroid carcinoma, especially in patients with positive TgAb..